Iron chelation by curcumin suppresses both curcumin-induced autophagy and cell death together with iron overload neoplastic transformation - Rainey, Nathan E. (Cell Death Discov, 2019)
Iron overload, notably caused by hereditary hemochromatosis, is an excess storage of iron in various organs that causes tissue damage and may promote tumorigenesis. To manage that disorder, free iron depletion can be induced by iron chelators like deferoxamine that are of increasing interest also in the cancer field since iron stock could be a potent target for managing tumorigenesis. Curcumin, a well-known active substance extracted from the turmeric rhizome, destabilizes endoplasmic reticulum, and secondarily lysosomes, thereby increasing mitophagy/autophagy and subsequent apoptosis. Recent findings show that cells treated with curcumin also exhibit a decrease in ferritin, which is consistent with its chemical structure and iron chelating activity. Here we investigated how curcumin influences the intracellular effects of iron overload via Fe-nitriloacetic acid or ferric ammonium citrate loading in Huh-7 cells and explored the consequences in terms of antioxidant activity, autophagy, and apoptotic signal transduction. In experiments with T51B and RL-34 epithelial cells, we have found evidence that curcumin-iron complexation abolishes both curcumin-induced autophagy and apoptosis, together with the tumorigenic action of iron overload.